A previously unreported potential malaria vector in a dry ecology of Kenya - Ogola, Edwin O.; Chepkorir, Edith; Sang, Rosemary; Tchouassi, David P. (Parasites & vectors, 2019)
Background In Kenya, malaria remains a major public health menace equally affecting the semi-arid to arid ecologies. However, entomologic knowledge of malaria vectors in such areas remains poor. Methods Morphologically-identified wild-caught Anopheles funestus ( s.l. ) specimens trapped outdoors from the semi-arid to arid area of Kacheliba, West Pokot County, Kenya, were analysed by PCR and sequencing for species identification, malaria parasite infection and host blood-meal sources. Results Three hundred and thirty specimens were analysed to identify sibling species of the An. funestus group, none of which amplified using the available primers; two were infected with Plasmodium falciparum and Plasmodium ovale , separately, while 84% ( n = 25) of the blood-fed specimens had fed on humans. Mitochondrial cytochrome c oxidase subunit 1 ( cox 1) and nuclear ribosomal internal transcribed spacer 2 (ITS2) sequences of 55 specimens ( Plasmodium -positive, blood-fed and Plasmodium -negative) did not match reference sequences, possibly suggesting a previously unreported species, resolving as two clades. Conclusions Our findings indicate the existence of yet-to-be identified and described anopheline species with a potential as malaria vectors in Kenya.